Open- and crowd-sourced MRV for agroforestry?: Preliminary results and lessons learned from a pilot study using Collect Earth to identify agroforestry on multiple land uses in Viet Nam and Colombia - Daniel, James; Tenneson, Karis; Suber, Marta; Mulia, Rachmat; Van Tranh, Phan; Arango, Jacobo; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Key messages ◼ Forty percent of developing countries plan to use agroforestry to meet climate and development goals, yet available systems for measurement, reporting and verification (MRV) are not capable of counting trees in agroforestry systems. ◼ Before agroforestry can become an important response to climate change, countries need access to affordable, accessible tools to improve their ability to monitor agroforestry. ◼ We evaluated the effectiveness of Collect Earth, an open-source platform that allows assessment of land use using freely available high-resolution imagery, for identifying primary types of agroforestry systems in Colombia and Viet Nam. ◼ Preliminary results are mixed but showed promise. Collect Earth is highly effective in identifying some easily distinguished types of agroforestry systems (such as agrisilviculture, boundary planting, and home gardens) but falls short with others (including some types of shadow and silvopastoral systems). ◼ Refinements to our approach—including the integration of local expertise into the photo- interpretation process— could help Collect Earth become a valuable tool to ensure that agroforestry trees count toward climate goals.